Damage to Pinus contorta in northern Sweden with special emphasis on pathogens - Karlman, Margareta (1986)
During a nine-year-period ca. 100 provenances of Pinus contorta were investigated annually with respect to different kinds of damage. primarily by parasitic fungi. Damage to Pinus contorta occurred mainly during the first ten years after planting. northern provenances of Pinus contorta were generally more resistant to pathogens than southern provenances. Weather damage occurred almost every year among trees of southern and coastal provenance. Trees of northern provenance also suffered from weather damage due to temperature oscillations during shoot elongation. Severe weather damage predisposed to infection by secondary pathogens. primarily Gremmeniella abietina. Even northern provenances of Pinus contorta were infected by Phacidium infestans in high-altitude stands in northern Sweden. Snow blight infection was. however. of less importance to lodgepole pine than to Scots pine. owing to the rapid early growth of the former. The most productive plants of both Pinus contorta and Pinus sylvestris were attacked by Phacidium infestans. So far vole damage has been the most severe threat to Pinus contorta in northern Sweden. Severe infection by Gremrneniella abietina was recorded after vole attack. even among northern provenances of lodgepole pine. Hitherto Pinus contorta has mainly been infected by the same fungi as Pinus sylvestris, with the exception of Melampsora pinitorqua and Lophodermella sulcigena.